3.8 dB Noise figure in bulk semiconductor optical amplifier - Bradley, Louise (My University, 2013)
The present paper reports numerical and experimental investigation of noise figure of a multi-section semiconductor optical amplifier. The designed amplifier shows a 3.8dB noise figure, which seems to be the lowest figure reported.
10th Conference on Lasers and Electro-Optics Pacific Rim (CLEO-PR)
PUBLISHED
Keywords: Semiconductor optical amplifiers; Noise figure; Noise; Standards; Charge carrier density; Educational institutions